Isolation and structure elucidation of triterpenes from inflorescence of banana (Musa balbisiana cv. Saba) - Thien , Hoe Seng; Charles Santhanaraju Vairappan; Chye , Fook Y; Takashi Kamada; Mohd Ismail Abdullah (Malaysian Society of Parasitology and Tropical Medicine, 2016)
The study aimed to isolate and elucidate the chemical compounds that are found in banana (Musa balbisiana cv. Saba) inflorescences. Banana inflorescence buds were extracted using methanol and the resulted methanolic extract was partitioned using chloroform, ethyl acetate and butanol against deionized water. The chloroform partition was further separated into fractions using column chromatography assisted by thin layer chromatography. The structure elucidation was performed using nuclear magnetic resonance spectrometry (NMR). Three triterpenes were isolated namely 31-norcyclolaudenone (1), cycloartenol (2) and (24R)-4a,24-trimethyl-5a-cholesta-8,25(27)-dien-3b-ol (3). This is the first report on the isolation of these triterpenes from Musa balbisiana inflorescence. The discovery of new triterpenes from banana inflorescence should be further explored to open a new perspective that banana by-products might serve as new source of natural products for food and pharmaceutical applications. Copyright of International Food Research Journal is the property of Universiti Putra Malaysia and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract.